A novel mobile biobehavioral regulation system for personalized trauma recovery support - Holly Matto; Padmanabhan Seshaiyer; Anna Newcomb; Shira Rothberg; Adriana Lopez-Piper (The Beryl Institute, 2019)
Even years after experiencing a physical trauma, individuals describe trauma-specific distress, as trauma triggers present as sensory reminders that initiate physiological reactions at time of exposure. Mobile technologies offer tremendous potential in helping individuals who have experienced trauma manage symptoms as they transition out of hospital care and move back into their communities where they are at risk of trauma trigger exposure. A personalized wearable device, tailored to a patient-specific diagnosis (e.g., PTSD) with programmable neurophysiological behavioral risk set-points, could be a useful tool in helping individuals monitor symptomology. When this type of monitoring device is also connected to a personalized recovery cue intervention on a smartwatch or phone, and activated when the wearable sensor detects heightened risk, there is the opportunity for in-the-moment symptom management. In this study we sought to understand the value for trauma survivors of using this type of personalized mobile recovery support system. Study participants were all trauma survivors or family members of survivors who were involved in the Trauma Survivors Network. A semi-structured interview was conducted with participants to understand perceptions on the utility, sensory experiences, and innovation insights of a mobile recovery sensory support system overall, and about the recovery cue intervention most specifically. Results from participant interviews inform the further development of our mobile recovery support system model in significant ways, suggesting that three components must be included: 1) Recovery cues; 2) Relationships (connecting to supportive network); and 3) Regulation (neurophysiological regulation and behavioral risk reduction). Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Innovation%20%26%20Technology%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens